Exploring factors associated with strain in carers of patients with traumatic brain injury - Boycott, Naomi E. (2010)
This study explored what factors are associated with strain in 48 carers of patients with traumatic brain injury (TBI). This was a cross-sectional cohort study of patients who were admitted to a Neurosurgical Unit with TBI over a period of nine years and followed up between five and 14 years post-injury. Their carers were assessed via postal survey for levels of strain using the Caregiver Strain Index (CSI) and asked for their perception of the patients’ disabilities using the family form of the Neurobehavioral Functioning Inventory (NFI). Elevated levels of strain were found in 42% of carers. Using logistic regression, outcome as rated by the patients’ GP on the Glasgow Outcome Scale (GOS) and all subscales of the NFI (except Somatic) contributed to explain 41 - 57% of the variance in strain, and predicted group membership correctly in 72.9% of cases. No individual variable contributed significantly to the explained variance in the model. The model was not significantly improved after removing outliers. Findings suggest that a number of factors combine to result in feelings of strain and illustrates the difficulty for clinicians to predict when strain may occur. The clinical implications of the study are discussed.